Protocatechualdehyde induced tumor suppressive autophagy through AMPK/ULK1 signaling pathway in gastric cancer - Ren, Mingming; Ma, Fangqi; Qin, Mengmeng; Sun, Xiaoyu; Wang, Yi; Zhu, Xiaohong; Xu, Yan; Cao, Nida; Zhao, Ruohan; Zhang, Yunchao; Zhu, Jiangchuan; Pan, Yongfu; et al. (Frontiers in Oncology, 2025)
BackgroundGastric cancer (GC) is one of the primary causes of cancer-related fatalities, which requires novel treatment including traditional Chinese medicine (TCM) to prolong survival. Protocatechualdehyde (PCA), a monomer from Chinese herbs, exhibits an anti-cancer effect by inhibiting proliferation and migration, or inducing apoptosis in various types of tumors. However, the anti-cancer effect and underlying mechanism of PCA in gastric cancer are still unclear.MethodsThe cell proliferation ability was detected by the cell counting kit-8 (CCK-8) and colony formation. The occurrence of autophagy was observed by TEM (Tansmission electron microscopy) and immunofluorescence. The expression of proteins involved in AMPK/mTOC1 signaling pathway was detected by western blotting. Apoptosis and cell cycle analysis were determined through flow cytometry. A xenograft mouse model was employed to validate the anticancer effect of PCA in vivo.ResultsPCA was first identified as a specific inhibitor to gastric cancer cells that significantly inhibited the proliferation of human gastric cancer cells MKN45 and AGS in a dose- and time-dependent manner, but not that of human gastric epithelial cells. Furthermore, PCA induced tumor suppressive autophagy in both gastric cancer cells, and blockage of the autophagy by silencing ATG5 can partially reverse the proliferation inhibition of PCA. Mechanistically, PCA induced-autophagy was largely dependent on the activation of the AMPK/ULK1 signaling pathway, and blockage of the pathway through AMPK specific inhibitor Compound C (Com C) or siRNAs targeting ULK1 prevented the occurrence of autophagy and partially reversed the proliferation inhibition induced by PCA. In addition, PCA significantly suppressed the growth of gastric cancer in the gastric cancer xenograft mouse model by activating key proteins related to the AMPK/ULK1 signaling pathway of autophagy.ConclusionThese findings demonstrated that PCA inhibited gastric cancer by inducing tumor suppressive autophagy through the AMPK/ULK1 signaling pathway. PCA may serve as a novel candidate for the treatment of gastric cancer.